Surfing about music - Cooley, Timothy J., 1962- (University of California Press, 2014)
"How are surfing and music interrelated? Is surfing inherently musical, as is sometimes claimed? Surfing about Music trace multiple connections between music and surfing through subjects ranging from mele (chants/songs) to hapa haole music in Hawaiỉ; from California "surf music" to surfing-themed festivals in Italy and the UK; from surf movie soundscapes to pro surfaces becoming pro musicians, as well as "soul surfers" making music on beaches. A lifelong surfer and musician himself, Cooley grounds his analysis in real-life stories, based on interviews and conversations with surfing musicians such as Jack Johnson, Tom Curren, and Dave Rastovich; surf movie makers including Bruce Brown and Andrew Kidman; and other surfer/musicians from Hawaiỉ, California, the United Kingdom, Italy, Australia, and elsewhere. This first expansive study of music and surfing broadens ethnomusicological thinking about the many ways musical activities are integral to human socializing beyond rigid notions of place and genre. Engaging, informative, and enlightening, this book is a fascinating exploration of surfing as a cultural practice with accompanying rituals, habits, and deeply held beliefs about why music is ess